Analysis of the Influence of Green Financing, Sustainability Report Transparency, and ESG (Environmental, Social, Governance) Implementation on Corporate Reputation in the Banking Industry in Indonesia - Loso Judijanto; Nanang Qosim; Rini Fitrianingrum (West Science Social and Humanities Studies, 2024)
This study examines the influence of green financing, sustainability report transparency, and ESG (Environmental, Social, Governance) implementation on corporate reputation in the Indonesian banking industry. Using a quantitative approach, data were collected from 75 respondents through a structured questionnaire, employing a Likert scale (1-5). The data were analyzed using SPSS version 26, with multiple regression analysis used to assess the relationships between the variables. The results reveal that green financing, sustainability report transparency, and ESG implementation all have significant positive effects on corporate reputation. Among these factors, ESG implementation has the strongest influence. These findings suggest that banks that adopt sustainable financial practices, maintain transparency in reporting, and integrate ESG principles are more likely to enhance their corporate reputation. The study provides insights for banking institutions and policymakers to prioritize sustainability initiatives in building public trust and improving competitiveness in the market.